2020
DOI: 10.1088/1367-2630/aba3e8
|View full text |Cite
|
Sign up to set email alerts
|

Wigner function and photon number distribution of a superradiant state in semiconductor heterostructures

Abstract: Advanced quantum technologies require sources of non-Gaussian and non-classical light. For the understanding of properties of quantum light it is necessary to reconstruct its quantum state. Here, we use time-domain optical homodyne tomography for the quantum state recognition and reconstruction of the femtosecond optical field from a nonequilibrium superradiant coherent electron–hole state formed in a semiconductor GaAs/AlGaAs heterostructure. We observe severe deviations from the Poissonian statistics of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Furthermore, superradiance has super-Poisson statistics and its Wigner functions have broad areas of negative values. This implies that superradiant pulses have a quantum nature [25]. In this work, it is experimentally demonstrated that the condensation of electrons and holes towards the bottoms of the bands, which occurs with the mediation of resonant photons during the superradiant phase transition, enables the realization of strong coupling and the observation of Rabi flopping.…”
Section: Optics and Laser Physicsmentioning
confidence: 84%
“…Furthermore, superradiance has super-Poisson statistics and its Wigner functions have broad areas of negative values. This implies that superradiant pulses have a quantum nature [25]. In this work, it is experimentally demonstrated that the condensation of electrons and holes towards the bottoms of the bands, which occurs with the mediation of resonant photons during the superradiant phase transition, enables the realization of strong coupling and the observation of Rabi flopping.…”
Section: Optics and Laser Physicsmentioning
confidence: 84%
“…Earlier work on quantum state tomography (QST) of SR pulses reported the Wigner function reconstruction in a pure displaced Fock state , n  [29], which is a non-classical photon state.…”
Section: Quantum State Tomographymentioning
confidence: 99%
“…We express n [entering n S (ω) through Eqs. (47)] through N by the same energy conservation law (4). Then, the population inversion N is the only unknown variable in Eq.…”
Section: Calculation and Analysis Of Optical Spectramentioning
confidence: 99%
“…Presently nanolasers are theoretically modeled either by rate equations as in [37,38], by numerical solution of the density matrix equations as in [22,[39][40][41], or by systems of equations for correlations as in the cluster expansion [25,42] or cumulant expansion [43,44] methods. Numerical analysis of superradiant emission and lasing has recently led to new and interesting results, such as mechanical effects in photon-atom interactions [45], lasing with a millihertz linewidth and rapid emitter number fluctuations [46], Wigner functions for semiconductor heterostructures [47], transition from superradiance to regular lasing by varying the coherent and incoherent driving [44], sub-and superradiance in multimode optical waveguides [48], and photon-antibunching in the fluorescence from an optical nanofiber-tip [49]. However, complementary analytical methods to model nanolasers without adiabatic elimination of polarization, that would apply to superradiant nanolasers, are not well developed.…”
Section: Introductionmentioning
confidence: 99%